Social mixing through densification? The struggle over the Little Mountain public housing complex in Vancouver - Rosol, Marit (DIE ERDE: Journal of the Geographical Society of Berlin, 2015)
In times of peak-oil and the on-going ‘urban renaissance’ (Porter and Shaw 2009), urban densification becomes increasingly more important. Densification is promoted not only for environmental reasons – in the sense of developing more compact and thus more sustainable cities – but also, as is the case in Vancouver, in the name of ‘social mixing’. Taking the conflict over “Little Mountain” – the oldest public housing complex in the province of British Columbia, Canada – as example, the article shows the conflicts that can arise in the process of densification. Despite the protests of residents and their supporters and without any concrete plans for redevelopment, almost all of the once 224 social housing units were demolished in 2009 to make room for at least 1,400 market condos (besides the 1-for-1 replacement of the social units). The example shows that densification processes that lack social measures for securing tenure for long-time residents lead to the displacement of poorer people, and to increased socio-spatial disparities. Furthermore, densification will not alleviate the affordability crisis but intensify it, if all the additionally created housing units will be market-housing only. Based on this example, the article shows that a purported social-mix policy is mainly motivated by recapturing prime real-estate, and identifies the rhetoric of ‘social mixing’ as ‘gentrification by stealth’ (Bridge et al. 2012).